Effects of Different Light Spectra on Oxidative Stress and Nutritional Quality of the Fish Plectropomus leopardus - Wensheng Li; Zheng Zhang; Baoliang Liu; Yingying Fang; Shuquan Cao; Wenyang Li; Yan Sun; Chengbin He; Chuanxin Zhang; Fan Fei (Fishes)
This study investigated the impacts of light spectra on oxidative stress and nutrient quality of the fish Plectropomus leopardus in indoor recirculating aquaculture systems. The fish (100 g ± 0.45 g [wet weight]) were cultures in five different light spectra (full-spectrum (400–800 nm), blue (450 nm), green (530 nm), red (630 nm), and dark) for 60 days. After experimentation, blood and muscle tissue were collected and analyzed for biochemical variables and nutritional quality. We demonstrated that the total cholesterol, triglycerides activities of P. leopardus in the dark groups were substantially elevated, relative to other groups (p < 0.05). Glutathione and glutathione peroxidase activities were elevated in the green light group versus other red groups, and cortisol was drastically reduced in the red group relative to other groups (p < 0.05). The crude ash concentration in the blue and full-spectrum group was substantially more elevated than in other groups (p < 0.05). Thr, Glu, Cys, Val, Met, Ile, Leu, Phe, Lys, His, Arg were markedly higher in the blue light versus the red light group (p < 0.05). The muscle of P. leopardus was rich in lysine and its essential AA index was in the order of blue light, full-spectrum, green light, dark and red group. The content of total saturated fatty acids in the blue light group was drastically lower relative to the dark, green and red groups (p < 0.05), and the total polyunsaturated fatty acids and DHA + EPA contents in the blue light group were substantially elevated relative to the other groups (p < 0.05). These results revealed that different light environments had certain effects on blood biochemical, antioxidant capacity, nutrient composition and proportion of P. leopardus. A comprehensive evaluation found that the blue light environment had more positive effects on the physiological, biochemical and nutritional quality of P. leopardus. This result provides a theoretical reference for the lighting strategy of an indoor recirculating aquaculture system.